Customer awareness towards promotional tools on ASNB products: perspective on student’s Faculty Business Management University Technology MARA Kampus Bandaraya Melaka / Noor Izzaida Abdul Halim - Abdul Halim, Noor Izzaida (Faculty of Business and Management, 2010)
The purpose of the study is to identify the relationship between promotional tools used by ASNB and customers awareness. Which means the independent variables and dependent variable are reach of the target audience, choice of media advertising, frequency of campaign and continuity of promotional tools and the dependent variables is customer’s awareness. This study also determined the level of awareness of respondents about ASNB products. Based on Pickton,David & Broderick, Amanda (2005), customer awareness can be creating due to reach, choice of media, frequency of campaign and continuity. Customer’s awareness among students Faculty Business Management UiTM Kampus Bandaraya Melaka is still low. According to the situation, the researcher has chosen 50 students from Faculty Business Management UiTM Kampus Bandaraya Melaka to be the respondents. In this study, the researcher has used exploratory, descriptive and causal research. Self-administered and interview questionnaires have been used in order to collect data from the respondents. Reliability test, frequency of distribution, cross tabulation, and hypotheses, has been used in this study to get the data from the questionnaires that been distributes to the respondents by using the Statistical Package for Social Science (SPSS). Finally, from the finding, it shows that all the independent variables has relationship with the dependent variable.